Apolitical Memory of Political Conflict : Remembering compulsory military service under Pinochet (1973-1990) - Leith Passmore (Nuevo mundo - Mundos Nuevos, 2016)
From the mid-2000s, advocacy groups representing ex-conscripts who served during the Pinochet dictatorship began to emerge. These groups grew and formed a loose movement that demanded recognition as victims and reparations for its members. A common sense of victimhood and a shared way of remembering military service evolved that was able to unite the cohort of nearly 100,000 former recruits that had mobilized by the end of 2013. This paper examines the challenge to Chile’s politicized memoryscape posed by a collective memory of military service under Pinochet that is apolitical. The context of its emergence, the memory politics of Chile’s post-transition decade, the political categories of victim and perpetrator, and the depoliticization of Chilean society more broadly meant ex-conscripts as individuals and as a movement had incentives to silence politics when they began to talk about their experiences. More fundamentally, however, ex-conscript memory is shaped less by Cold War rivalries or local political struggle than by ideas of patriotism, masculine identity, work, family values, and poverty that remained relatively constant throughout the twentieth-century and independent of trajectory of political and ideological conflict. Historicizing twenty-first-century memory of military service under Pinochet therefore requires turning to the apolitical.